PERSEPSI MASYARAKAT TERHADAP PERANAN PUNGUAN PARSAHUTAON DOS ROHA DALAM PELESTARIAN TRADISI PERKAWINAN MASYARAKAT BATAK TOBA PERANTAU DI DESA TANAH MERAH KECAMATAN SIAK HULU - Renni Panjaitan; Hambali Hambali; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study aims to determine people's perceptions of the role Parsahutaon levies in the preservation of the Toba Perantau Batak community marriage tradition in DesaTanah Merah , Kecamatan Siak Hulu . The total population in this study was the entire community of Toba Batak tribes who were married in DesaTanah Merah, Kecamatan Siak Hulu , amounting to 186 families and the sample of this study amounted to 18 families. Data collection techniques are questionnaires, interviews, observations, and documentation. Data analysis using Descriptive Quantitative. The results showed that data on public perceptions of the role of the Parsahutaon Dos Roha Collection in the Pelesratian Marriage of the Toba Perantau Batak Society in Desa Tanah Merah , Kecamatan Siak Hulu as a whole from 18 respondents stated Yes. This is appropriate in the percentage of 70.20% said to be "Good", 15.65% of respondents perceive sometimes and 13.38% of respondents have never shared the role of Parsahutaon Dos Roha's Levies in Preservation of the Toba Perantau Batak Community Marriage Tradition in Desa Tanah Merah Kecamatan Hulu. Thus it was concluded that the Community Perception of the Role of Parsahutaon Dos Roha in Preserving the Marriage Tradition of the Toba Perantau Batak Community in Desa Tanah Merah, Kecamatan Siak Hulu was Good. That is 70,20 % according to the benchmark number of those who answered Yes in the range of 66.67% -100% "GOOD.Keywords: Perception, Parsahutaon Levies, Preservation of Marriage Traditions